The 400-Meter Walk Test to Evaluate Walking Performance between Diabetics and Healthy Females - Ronald Pakasi; Angela BM Tulaar; Sarwono Waspadji; Corrie Wawolumaya (Indonesian Journal of Physical Medicine & Rehabilitation, 2013)
Objective: to evaluate walking performance in female with type 2 diabetes mellitus (DM2) with the 400-meters walk test (400-MWT) compared to healthy individuals.Methods: two groups of female subjects with DM2 and healthy individuals were matched by the age. The 400-MWT parameters to be compared were walking speed (WS) and predicted maximum oxygenconsumption (pVO2max). Baseline examination included body mass index (BMI), random blood glucose (RBG), and ankle-brachial index (ABI). All subjects performed 2 minutes warm up before thetest. Heart rate (HR) was recorded every 30 seconds, and blood pressure (BP) was measured before warm up and within 60 seconds after test. The test was performed twice on a different day.Results: Nineteen subjects on each group participated in the study. The mean WS was significantly different (p<0.0001) between the study group (1.26 + 0.19 and 1.31 + 0.17 m/s) and the control group(1.70 + 0.20 and 1.78 + 0.24 m/s) for the first and second tests respectively. There was a significant difference of mean pVO2max (p<0.0001) between the study group (17.22 + 2.94 and 17.99 + 2.36 ml/kg/min) and the control group (23.68 + 3.79 and 24.44 + 3.74 ml/kg/min).Conclusion: the 400-MWT demonstrated lower walking performance in female subjects with DM2 compared to healthy individuals.Keywords: Type 2 DM, healthy individuals, 400 meter walk test, walking speed, VO2max.